„TECHNINIS ŽODIS“: MOBILUS IR KODUOTAS. - KETURAKIS, SAULIUS (Logos: A Journal, of Religion, Philosophy Comparative Cultural Studies & Art (08687692), 2020)
The article discusses the intrusion of the mechanism into the processes of writing (usually literary writing) and some of its consequences. The research starts with the discussion about the interaction between the written word and mobile media, when the writer and the reader are in a constantly unstable and changing environment. The study ends with radically technologized forms of linguistic communication, where the literary text is first written in computer-readable programming languages, and then, when needed, the programme generates a regular literary text.